Alpha-1-antitrypsin protects vascular grafts of brain-dead rats against ischemia/reperfusion injury - Ding, Qingwei; Loganathan, Sivakkanan; Zhou, Pengyu; Sayour, Alex Ali; Brlecic, Paige; Radovits, Tamás; Domain, Roxane; Korkmaz, Brice; Karck, Matthias; Szabó, Gábor; Korkmaz-İçöz, Sevil (Journal of surgical research, 2023)
Introduction - Endothelial dysfunction is a potential side effect of brain death (BD). Ischemia/reperfusion (IR) injury during heart transplantation may lead to further endothelial damage. Protective effects of alpha-1-antitrypsin (AAT), a human neutrophil serine protease inhibitor, have been demonstrated against IR injury. We hypothesized that AAT protects brain-dead rats’ vascular grafts from IR injury. - Methods - Donor rats were subjected to BD by inflation of a subdural balloon. After 5.5 h, aortic rings were immediately mounted in organ baths (BD, n = 6 rats) or preserved in saline, supplemented either with vehicle (BD-IR, n = 8 rats) or AAT (BD-IR + AAT, n = 14 rats) for 24 h. During organ bath experiment, rings from both IR groups were exposed to hypochlorite to simulate warm reperfusion-associated endothelial injury. Endothelial function was measured ex vivo. Immunohistochemical staining for caspases was carried out and DNA-strand breaks were evaluated using terminal deoxynucleotidyl transferase-mediated dUTP nick-end labeling. Data are presented as median (interquartile range). - Results - AAT improved IR-induced decreased maximum endothelium-dependent vasorelaxation to acetylcholine in the BD-IR + AAT aortas compared to the BD-IR group (BD: 83 (9-28) % versus BD-IR: 49 (39-60) % versus BD-IR + AAT: 64 (24-42) %, P < 0.05). Additionally, an increase in the rings’ sensitivity to acetylcholine was noted after AAT (pD2-value: BD-IR + AAT: 7.35 (7.06-7.89) versus BD-IR: 6.96 (6.65-7.21), P < 0.05). Caspase-3, -8, -9, and -12 immunoreactivity and the number of terminal deoxynucleotidyl transferase-mediated dUTP nick-end labeling-positive cells were significantly decreased by AAT. - Conclusions - AAT alleviates endothelial dysfunction, prevents increased caspase-3, -8, -9, and -12 levels, and decreases apoptotic DNA breakage due to BD and IR injury. This suggests that AAT treatment may be therapeutically beneficial to reduce IR-induced vascular damage.
Online verfügbar: 9. Dezember 2022
Gesehen am 10.08.2023